Transport of aguardiente to Callao, by the South Sea, 1777 (Palimpsesto, 2017)
A new tax of 12½ % was enacted in July 1777 on aguardiente that entered the port of Callao, transported by ships that sailed the South Sea. The registration of the tax revenue in fiscal books, from that day until the end of the year, offers numerous data, such as the ships’ date of entry, its name, place of embarkation, the number of pots that contained aguardiente, its origin, denomination and value, as well as the consignees of the product, all of which contribute to further the research on variables relevant to the history of this distillate, which allows for some documented statements.
Keywords: aguardiente; maritime transport; 18th century; South Sea; canisters; El Callao